COMPARISON ANALYSIS OF INPUT AND OUTPUT POWER ON INVERTERS OF DIFFERENT TYPES WITH PARARIZED LOADS - Bagastira, Raihan; Harahap, Partaonan; Oktrialdi, Benny; Balisrannislam, Balisrannislam (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The increasing use of electrical energy in homes has resulted in the use of fuel being very depleted, to overcome this problem there must be savings in electrical energy by using an inverter. The inverter is able to convert 12V DC (unidirectional) electricity into 220V 50Hz AC (alternating) electricity. The evaluation of the best inverter and having input and output power efficiency for various types of loads can be seen from the wave output generated. For resistive loads, the average efficiency of the Type A inverter is 38.7%, the Type B inverter has an average of 45.4% and the inductive load on the Type A inverter is 32.8%, for the Type B inverter, it is 81.1 % and the capacitive load on the Type A inverter is 5.3% and the Type B is 62.8%.